The Open Door era : United States foreign policy in the twentieth century - Cullinane, Michael Patrick, 1979-; Goodall, Alex (Alexis Vere) (BAAS paperbacks., 2017)
In 1899, U.S. Secretary of State John Hay wrote six world powers calling for an 'Open Door' in China that would guarantee equal trading opportunities, curtail colonial annexation, and prevent conflict in the Far East. Within a year, the region had succumbed to renewed colonisation and war, but despite the apparent failure of Hay's diplomacy, the ideal of the Open Door emerged as the central component of U.S. foreign policy in the twentieth century. Just as visions of 'Manifest Destiny' shaped continental expansion in the nineteenth century, Woodrow Wilson used the Open Door to make the case for a world 'safe for democracy', Franklin Roosevelt developed it to inspire the fight against totalitarianism and imperialism, and Cold War containment policy envisioned international communism as the latest threat to a global system built upon peace, openness, and exchange. In a concise yet wide-ranging examination of its origins and development, readers will discover how the idea of the Open Door came to define the American Century.